2011
DOI: 10.1007/s13410-011-0038-y
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of pre-diabetes and associated risk factors in an adult Omani population

Abstract: The Sultanate of Oman has experienced an epidemiological transition over the last 4 decades with rising tide of non-communicable disease such as type-2 diabetes. This study aims to estimate the prevalence of prediabetes and explore the associated demographic, clinical and biochemical risk factors among a semi-urban Omani population. A semi-urban satellite town, Bidbid, located about 30 km west of the capital, Muscat, was selected as the study setting. The targeted participants were Omani adults (18 to 60 years… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 39 publications
1
11
4
Order By: Relevance
“…32,33 Also, some studies observed that the Predictors of pre-diabetes are male, old-age, high socio-economic status, low education level, hypertension, obesity, central obesity, and smoking. 34 Moreover another study also has the same results; reported overweight adolescents had a 2.6-fold higher rate than those with normal weight (1.3-5.1). 27 In multivariate analyses, an independent correlate of pre-diabetes was low exercise, which is in agreement with our results.…”
Section: Discussionmentioning
confidence: 56%
“…32,33 Also, some studies observed that the Predictors of pre-diabetes are male, old-age, high socio-economic status, low education level, hypertension, obesity, central obesity, and smoking. 34 Moreover another study also has the same results; reported overweight adolescents had a 2.6-fold higher rate than those with normal weight (1.3-5.1). 27 In multivariate analyses, an independent correlate of pre-diabetes was low exercise, which is in agreement with our results.…”
Section: Discussionmentioning
confidence: 56%
“…Emerging evidence suggests that people identified in a prediabetic status could be given health education to arrest or reverse progression of diabetes. [14] The percentage of Saudi subjects who had an impaired fasting glucose (IFG) in the range 6.1-7.0 mmol/L was 14.7% in 2007 [15] ; however, our study in 2013 came up with a prevalence of prediabetes (23.6%) among adult Saudi population.…”
Section: Discussionmentioning
confidence: 61%
“…Type 2 diabetes is the world's fastest growing public health problems, with 366 million anticipated to fulfil the diagnostic criteria by 2030. [13,14] Out of the respondents, 37.7% were with high school education, and 38.6% were house wives.…”
Section: Discussionmentioning
confidence: 99%
“…Prediabetes is the risk factors for various diseases and complications [8,11,12] . It may affect various metabolic pathways which are taking place in the liver [13] .…”
Section: Discussionmentioning
confidence: 99%